COENZYME Q10 IN THE COMPLEX TREATMENT OF ARTERIAL HYPERTENSION - Yu. P. Pereponov (Российский кардиологический журнал)
Increasing incidence of arterial hypertension (AH) justifies the need for more effective AH treatment and prevention. Pharmaceutical therapy remains the basis of AH management. The most modern and effective variant of pharmaceutical AH management is combination treatment, as confirmed by the data from multiple clinical trials. Antihypertensive agents could be combined with metabolic medications, in particular, ubiquinone – coenzyme Q10 (Kudesan). This agent optimises electron transport in the cytochrome chain, improves tissue energy balance, and demonstrates antioxidant activity. Moreover, several studies have shown antihypertensive effects of this medication. In addition, coenzyme Q10 is virtually free from adverse effects. The available evidence supports the clinical use of coenzyme Q10 (Kudesan) for AH treatment.